ASSESSMENT ON MARKING SPECIFICATION OF REAR SIDE OF HEAVY GOODS VEHICLES IN MALAYSIA - Yahya, Siti Aishah; Ramli, Nor Azam; Shith, Syabiha; Rasli, Nur Baitul Izati (International Journal of Research -GRANTHAALAYAH, 2020)
A vehicle’s conspicuity is determined by the colour and pattern of painted surfaces, height, lighting system, reflectorization and fluorescent markings. In Malaysia, the better visibility of heavy goods vehicles has to be marked with retroreflective marking. The objectives of the study to analyse percentages of marking requirement that compliant with the MS 828:2011. The study was conducted at Jawi Toll Plaza, Nibong Tebal, Pulau Pinang from 9.00 a.m. to 5.00 p.m for three days. As a result, the highest compliance level of marking requirement was 96% which is box truck two axles. Meanwhile, other categories were between 17% to 91%. Many HGVs were not installing rear-end marking type 5, while all trucks and trailers with a maximum gross vehicle weight (GVW) of 3500 kg and above had to be marked with Type 5 (contour marking) as of 1 July 2019. Some improvement needed to reduce the severity and the number of road accidents by recommended a safe following distance.